Cafeteria No. 2 (1953)
Caption reads: 'Cafeteria No. 2, located adjacent to one group of campus dormitory units, can seat 350 at one time. Kitchen facilities are adequate to serve 700 in an hour.' Back of photo reads: 'Dining Facilities: Dining Hall No. 1-Interiors: Seating (1953)'